Features for Discriminating Normal Cases in Mass Screening for Gastric Cancer with Double Contrast X-ray Images of Stomach. Issue 6 (2014) - Abe, Koji; Nakagawa, Hideaki; Minami, Masahide; Tian, Haiyan
No abstract available